Reduced kinase activity of polo kinase Cdc5 affects chromosome stability and DNA damage response in S. cerevisiae. Issue 21 (1st November 2016) - Rawal, Chetan C.; Riccardo, Sara; Pesenti, Chiara; Ferrari, Matteo; Marini, Federica; Pellicioli, Achille
ABSTRACT: Polo-like kinases (PLKs) control several aspects of eukaryotic cell division and DNA damage response. Remarkably, PLKs are overexpressed in several types of cancer, being therefore a marker of bad prognosis. As such, specific PLK kinase activity inhibitors are already used in clinical trials and the regulation of PLK activation is a relevant topic of cancer research. Phosphorylation of threonine residues in the T-loop of the kinase domain is pivotal for PLKs activation. Here, we show that T238A substitution in the T-loop reduces the kinase activity of Cdc5, the only PLK in Saccharomyces cerevisiae, with minor effect on cell growth in unperturbed conditions. However, the cdc5 -T238A cells have increased rate of chromosome loss and gross chromosomal rearrangements, indicating altered genome stability. Moreover, the T238A mutation affects timely localization of Cdc5 to the spindle pole bodies and blocks cell cycle restart after one irreparable double-strand break. In cells responding to alkylating agent metylmethane sulfonate (MMS), the cdc5 -T238A mutation reduces the phosphorylation of Mus81-Mms4 resolvase and exacerbates the MMS sensitivity of sgs1 Δ cells that accumulate Holliday junctions. Of importance, the previously described checkpoint adaptation defective allele, cdc5 -ad does not show reduced kinase activity, defective Mms4 phosphorylation and genetic interaction with sgs1 Δ. Our data define the importance of regulating Cdc5 activity through T-loop phosphorylation to preserve genome integrity and respond to DNA damage.